Influence of operating conditions on chemical composition of particulate matter emissions from residential combustion - Vicente, E. D.
Wood combustion experiments were carried out in a Portuguese woodstove to determine the effects of biofuel type, ignition technique, biomass load and cleavage, as well as secondary air supply, on the chemical composition of particles (PM10). Two typicalwood fuels in the Iberian Peninsulawere tested: pine (Pinus pinaster), a softwood, and beech (Fagus sylvatica), a hardwood. PM10 sampleswere analysed for organic and elemental carbon (OC and EC), levoglucosan and 56 elements. Total carbon (TC) represented 54–73 wt.% of the particulate mass emitted during the combustion process, regardless of wood species burned or operating condition tested. The carbonaceous component of PM10 was dominated by OC. The OC content of PM10 was higher when higher loads were fed into the combustion chamber, for both fuels. EC represented from 8 to 35 wt.% of the particulate mass. OC/EC ranged from 1.1 to 6.1 (avg. 3.0 ± 1.8) for pine combustion and from 1.1 to 3.4 (avg. 2.0 ± 0.8) for beech combustion. The lowest OC/EC ratios for both woods were observed for ignition from the top. Levoglucosanwas found in all samples, representing from3.7 to 7.5wt.% and from4.2 to 8.9wt.% of PM10emitted from the combustion of pine and beech, respectively. The use of low loads of fuel generated high amounts of levoglucosan either for pine or beech. Altogether, trace elements obtained by ICP-MS and ICP-AES comprised from 0.46 wt.% to 1.41 wt.% and from 0.87 wt.% to 2.36 wt.% of the PM10 mass for pine and beech combustion, respectively. Among elements, K, Ca, Na, Mg, Fe and Al contributed to more than 75% of the total ICP-MS mass. Potassium was the major element in almost all PM10 samples.